2023
DOI: 10.3389/fpsyg.2023.1092893
|View full text |Cite
|
Sign up to set email alerts
|

Meaning in life and smartphone addiction among Chinese female college students: The mediating role of school adjustment and the moderating role of grade

Abstract: BackgroundThe fact that female college students are more addicted to smartphones than male college students has raised public concerns. However, previous studies have rarely explored the mechanism of female college students’ smartphone addiction. Previous studies have shown that identity may affect the formation process of female college students’ smartphone addiction, and the identity of female college students in different grades may be different. Nonetheless, few studies have explored the grade differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…All these strategies could be conducive to reduce the risk of anxiety and SPA [ 58 ]. By contrast, individuals with lower levels of EI would tend to think about the future negatively, feel uncertain about what may happen to them in future, find no meaning in life, and are more likely to escape into smartphone or indulge in others social medias [ 93 ]. Using these new social medias might relieve their negative feelings about future tasks and decisions.…”
Section: Discussionmentioning
confidence: 99%
“…All these strategies could be conducive to reduce the risk of anxiety and SPA [ 58 ]. By contrast, individuals with lower levels of EI would tend to think about the future negatively, feel uncertain about what may happen to them in future, find no meaning in life, and are more likely to escape into smartphone or indulge in others social medias [ 93 ]. Using these new social medias might relieve their negative feelings about future tasks and decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Contrariwise, if college students lack MIL, they are likely to have school adjustment problems and show depression and negativity. In order to relieve negative emotions and make up for inner emptiness, college students are easily addicted to the “virtual network world” of smartphones ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, some scholars verified that MIL could indirectly affect college students’ SA through self-control ( 31 ). In addition, a recent research has shown that MIL can indirectly affect college students’ SA through school adjustment ( 32 ). Summarizing the above literature, many scholars have made beneficial investigations on the relationship between MIL and college students’ SA, but these studies only investigated the influence of MIL on college students’ SA, and all the studies were cross-sectional rather than follow-up studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Empirical research results also show that since there are inexhaustible videos and games in smart-phones, the individuals with a lower sense of meaning in life are more likely to become addicted to them. 19 Correspondingly, when college students have enhanced their sense of meaning in life, it is expected that their mobile phone addiction can be further mitigated. Based on this, this study proposes hypothesis 3: The sense of meaning in life has a mediating effect on the relationship between mindfulness training and mobile phone addiction.…”
Section: Introductionmentioning
confidence: 99%